Perbandingan Kinerja Keuangan Menggunakan Risiko Pasar pada PT PAN Indonesia Bank Sebelum dan Selama Covid-19 Periode 2017-2022 - Joestantika, Bernadeth Lintang; Kusmargiani, Ida Savitri; Muslikh, Moh. (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2024)
This research aims at determining the difference in the results of market risk assessments at PT Pan Indonesia Bank Before and During Covid-19 Period 2017-2022. The data used in this research are secondary data obtained from the Financial Statements of PT Pan Indonesia Bank. The data analysis method used is Inherent Risk Assessment of Market Risk in accordance with SEBI No.13/24/DPNP and SEOJK No.14/SEOJK.03/2017. The results in this research show that there are differences in the acquisition of market risk of PT Pan Indonesia Bank Before and During Covid-19. Market risk rating before Covid-19 (2017-2019) is rating 1 (Low) in 2017 then increased to a rating of 2 (Low to Moderate) in 2018 and fell again in 2019 to a rating of 1 (Low). Meanwhile, During Covid-19 (2020-2022) bank's market risk stabilized with a rating of 1 (Low).